The Impact of the Menstrual Cycle on Sports Performance: A Narrative Review - Dudek, Stanisław; Koziak, Weronika; Kornacka, Agata; Bętkowska, Aleksandra; Makieła, Michalina; Dudek, Wojciech; Szostak, Kamila; Tomaka, Rafał; Byra, Anna (Quality in Sport, 2025)
Background The menstrual cycle (MC) plays a fundamental role in female physiology, influencing endurance, strength, and overall athletic performance. Hormonal fluctuations across the menstrual phases impact metabolism, muscle recovery, thermoregulation, cardiovascular function, and psychological well-being. Recognizing these variations is crucial for optimizing training and competition strategies for female athletes. Objective This review synthesizes recent scientific findings on the effects of MC phases on athletic performance, specifically examining endurance, strength, neuromuscular function, and perceived exertion. Methods A review of peer-reviewed literature was conducted using databases such as PubMed, Scopus, Web of Science, and Google Scholar. Results Hormonal fluctuations across the menstrual cycle influence endurance, strength, and perceived performance. The follicular phase supports muscle recovery, neuromuscular efficiency, and cardiovascular function, potentially enhancing performance, though increased ligament laxity may raise injury risk. During ovulation, energy availability improves, but joint laxity increases susceptibility to injury. The luteal phase introduces physiological challenges such as elevated core temperature, cardiovascular strain, and increased perception of effort, which may impair endurance. Despite these complexities, current evidence does not support a one-size-fits-all approach to training modifications based on the menstrual cycle. Instead, individualized menstrual tracking and adaptive training strategies may offer more effective ways to optimize female athlete performance.